Programy kształcenia Katedry Bibliotekoznawstwa i Informacji Naukowej Uniwersytetu Łódzkiego w latach 1945-2011 - Kowalewska, Urszula; Mikołajuk, Lidia (Acta Universitatis Lodziensis. Folia Librorum, 2013)
The paper presents the development of educational programs of the Chair of Library and Information Science at the University of Lodz. It also gives a brief overview of evolving its syllabuses. The comparative analysis of LIS programs is performed. The similarities and differences between higher education LIS systems in the past are described. The curriculum must have been adapted to new professional standards. The Chair of Library and Information Science have changed its syllabuses in conformity with the amended Act on Higher Education.